THE COLLECTION OF SUBSIDIZED LOANS FOR MICRO-ENTREPRENEURS IS IN TERMS OF INTEREST RATES, SERVICE QUALITY AND CREDIT PROCEDURES AT PT. BPR BKK TULUNG PERSERODA KLATEN REGENCY - Dinawati Retnaningrum; Bambang Mursito; Ida Aryati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of interest rates, service quality and credit procedures on taking subsidized credit at PT BPR BKK TULUNG (Perseroda) Klaten Regency. This research method uses a quantitative research design. The population in all customers of micro business actors who take subsidized credit at PT BPR BKK TULUNG (Perseroda) Klaten Regency, amounting to 200 customers The sampling technique used in this study is random sampling technique with a sample of 100 customers. Collecting data by using a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results showed that interest rates, service quality and credit procedures had a positive and significant effect on taking subsidized credit at PT BPR BKK TULUNG (Perseroda) Klaten Regency. Suggestions from this research, PT BPR BKK TULUNG (Perseroda) Klaten Regency continue to maintain and increase interest rates, service quality and existing credit procedures, so that it will make subsidy credit taking increase and be better than before. Keywords: Subsidized Loans, Interest Rates, Service Quality, Credit Procedures